Recruiting CEOs in Local Government: A 'Game of Musical Chairs'?. Issue 4 (14th December 2016) - Hutchinson, Jacquie; Walker, Elizabeth; McKenzie, Fiona Haslam
Abstract: This article focusses on leadership in local government and the attributes valued in a CEO. It draws on a series of interviews with both Mayors/Shire Presidents and incumbent CEOs undertaken as the local government sector is faced with a number of complex challenges that is expanding the traditional role and responsibilities from the regulated organisational delivery of 'rates, roads, and rubbish', to one that is involved in long‐term more market‐driven delivery of a diverse range of services. The analysis raises the question as to whether both political and organisational leaders have fully understood the impact of the changing sector, and the consequential type of organisational leadership required. Further, the article argues that long established formal power structures and processes of local government and specifically the apparent unencumbered power of Mayors and elected members over all aspects of CEO employment, especially recruitment, may in fact compromise leadership appointments and organisational performance. Abstract : This article reports on a study that investigates what elected and appointed officials believe are necessary attributes for appointment to the role of local government CEO and the processes used to recruit suitable candidates. The findings highlight two distinct types of leadership that reflect very different concepts of local government.